Le rôle de l'avocat dans l'enquête moderne

(untitled) (Faculté de droit de l’Université Laval, 1977)
N.D.L.R. Le 10 septembre 1976, la Faculté de droit de l'Université Laval, le Barreau du Québec et la Magistrature ont tenu, en la ville de Québec, une séance conjointe de rentrée des tribunaux et d'ouverture de l'année académique. Comme par le passé, nous publions des extraits à la fois des exposés alors prononcés et de l'échange des points de vue y ayant fait suite. At a joint meeting held last September for the opening of the courts and the new academic year, Members of the Quebec Bar and Bench and law teachers of Laval University expressed their views on the part lawyers are now called upon to play in present day inquiries. We here publish extracts of the principal views verbally given on the subject.